2020
DOI: 10.31083/j.ejgo.2020.04.4932
|View full text |Cite
|
Sign up to set email alerts
|

Is 3D printing-gided three-dimensional brachytherapy suitable for cervical cancer: from one single research institute?

Abstract: Objective: To investigate the guidance value of 3D printing in brachytherapy for cervical cancer and its role in the doctorpatient communication. Results: The median followup time was 36 months (1063); 3D models of 50 patients with cervical cancer were successfully printed out. Fifty patients underwent 255 times the source applicator. EQD 2 of HRCTV D90, bladder D2cc, sigmoid

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 18 publications
0
10
0
Order By: Relevance
“…Title and abstract screening was performed by the reviewers leaving 120 studies for assessment of full text for eligibility. Eighty-eight studies were excluded for the following reasons: models were not patient speci c (52), articles were duplicates (17), not the correct patient population (8), models were not printed (7), not in English (2), non-human models (1), and/or could not be accessed (1). In total 32 studies were included for review.…”
Section: Study Selectionmentioning
confidence: 99%
See 4 more Smart Citations
“…Title and abstract screening was performed by the reviewers leaving 120 studies for assessment of full text for eligibility. Eighty-eight studies were excluded for the following reasons: models were not patient speci c (52), articles were duplicates (17), not the correct patient population (8), models were not printed (7), not in English (2), non-human models (1), and/or could not be accessed (1). In total 32 studies were included for review.…”
Section: Study Selectionmentioning
confidence: 99%
“…Two studies have also shown bene t of 3D printed patient speci c models for brachytherapy planning. 51,52 In these studies, 3D printed patient speci c models were effective and non invasive for pre-planning brachytherapy in patients with cervical cancer. 51,52 Physicians using the models, reported high delity and usefulness, and their overall evaluation of the cer vical cancer model was 8.0 ± 0.8 points.…”
Section: Surgical Planningmentioning
confidence: 99%
See 3 more Smart Citations